Rice milling quality as affected by drying method and harvesting time during ripening in wet and dry seasons. (2nd January 2019) - Xangsayasane, Phetmanyseng; Vongxayya, Khamtai; Phongchanmisai, Senthong; Mitchell, Jaquie; Fukai, Shu
ABSTRACT: Head rice recovery is known to decrease with the delay in harvesting during ripening, but this effect may differ between wet season (WS) and dry season (DS) and among different paddy drying methods. In five experiments, rice was harvested by hand between 25 and 45 days after flowering in DS and WS when temperature around harvest was slightly above and below 30°C, respectively. The highest head rice recovery was generally obtained when rice was harvested at 25 days after 75% flowering. Delaying harvest to 30 days resulted in significant reduction in head rice recovery in 3 out of 7 cases and further delay to 35 days resulted in significant reduction in 8 out of 10 cases. For the crops harvested 25 days after flowering and dried with a flatbed dryer head rice recovery improved compared to sun drying in two experiments. When harvesting was delayed, sun drying tended to reduce head rice recovery compared to artificial drying. Sun drying only in the morning also improved head rice recovery compared to drying for the whole day. For a given drying method, head rice recovery decreased with increase in heat sum from flowering to harvest. It is concluded that rice crops should be harvested in both DS and WS around 25 days after 75% flowering when heat sum with base temperature of 10°C was around 450–500 degree-days. If an artificial dryer is not available, rough rice should be sun dried only in the morning with frequent stirring and mixing to promote more even drying. Abbreviations: WS: wet season; DS: dry season